Cutaneous merkel cells in porcine and human tissue expansion - Wollina, U... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1993)
Merkel cells (MC) act as mechanical transducers and paracrine cells of the skin. MC were identified in human and porcine skin by immunoperoxidase technique with monoclonal antibody Cam 5.2. We compared the epidermal MC frequency in expanded and non-expanded skin since tissue expansion causes a change of mechanical forces. For human skin, MC density in nonexpanded epidemzis was 21.3 19.9 per square mm for transversal sections and 7.5 17.5 per square mm for upsidedown preparations of epidezmal sheets. The values for expanded skin were 14.4 21.5 and 12.7 10.4 per square mm skin surface (p great. th. 0.05). In porcine epidermal sheets 5.5 5.5 MC per square mm skin surface were estimated, in the expanded samples 1.6 2.1 (p great. th. 0.05). Skin surface area, however, was markedly enlarged. W ithin the anagen hair follicles, MC were present in the outer hairroot sheath. MC were concentrated in the bulb region, the bulge area and pars infundibularis. The distribution pattern of hair follicle MC remained unaftected by tissue expansion. These findings suggest a de novo formation of epidermal MC during tissue expansion of human and porcine skin.
Keywords: Anatomy and histology; Cell count; Epidermis; Hair; Immunoenzyme techniques; Isolation and purification; Keratin; Mechanoreceptors; Physiology; Skin; Surgery; Swine; Tissue expansion